Articulatory characteristics of the occlusion phase of /tS/ compared to /t/ in adult speech - Liker, Marko; Gibbon, Fiona E.; Wrench, Alan Horga, Damir (2007)
This study used electropalatography (EPG) to investigate articulatory characteristics of /tS/ and /t/ occlusion in order to provide normative data to be used for the diagnosis and treatment of individuals with speech disorders. EPG data from the EUR-ACCOR database were analysed for nonsense VCV sequences containing /t / and /t/ in nine vowel contexts for seven English speaking adults. The main results of this study are that all speakers had a significantly more posterior placement for /t / compared to /t/ and that placement was stable during the occlusion phase of both /t / and /t/. For most speakers, the occlusion phase was longer for /t / compared to /t/, the occlusion phase generally involved more EPG contact and was slightly more variable in /t / compared to /t/, but these differences were not statistically significant for all speakers. The implications of the results for diagnosing and treating speech disorders are discussed.
Projekt MZOS
ENG